PENEGAKAN HUKUM YANG BERORIENTASI PADA KEBERLANJUTAN SUMBER DAYA IKAN - Rochmani Rochmani (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Area of Indonesia consists of 80% water, which contains abundance of potential fish resources, Those fish resources should be utilized for as much as prosperity and welfare for Indonesian. In fact, fish resourceshaven’t enhanced the living standard, which is sustainable and equitable. Issues on fisheries come up such as exaggeration of fishing, theft fish, illegal fishing activities and the use of fish resources that exceeding thegeneration of fish itself. That circumstance will cause harm for the state, the fishermen, as well as people in general. The use of tools that harm the nature will cause the decrease of fish resources and threat thesustainability of fish resources. The aim of writing this article is to analyze law enforcement related to the sustainability of fish resources and the sustainability of fish resources, viewed from the perspective of justice.As the result of the study, law enforcement to protect the fish resources generally has not given attention to the sustainability of fish resources, therefore fishermen still use unfriendly tools to catch the fishes. Thoseunfriendly tools will cause the occurrence of over-fishing and will impact to the environmental damages. Those kinds of things will destruct the fishes, therefore the quantity of fish will have deteriorated and evencould be extinct. Those environmental damages would suffer the present generation as well as the next generation since they couldn’t consume fish which is very essential for the growth of the human body anderadicate the job for the people as the fishermen. The present generation will be sinful if the next generation will get the impact of what the present generation done. In order to reduce more over-fishing activities and the distrust of the fish habitat it needs the law enforcement, which is oriented to the sustainability of fish resources. The sustainability of fishery resources couldn’t maintain its existence, this could be seen as the symbol of environmental damages. In this case, the law also needs to make integration of fish resources sustainability to be processed so that it will result output law enforcement which is oriented to fish resourcessustainability. As a conclusion, in law enforcement oriented to fish resources sustainability, it needs to be thought by the lawmaker to embed that the law should contain idea or concept about justice, legal certainty,the significance of fish resources and the implementation of the law itself. In the fish resources utilization and law enforcements, it needs to pay attention to the justice principle; intergenerational equity; intergenerational equity; precautionary; conservation of biological diversity; conservation of biological diversity.